1 + 1 < 2! Effects of Social Media Engagement and Advertising on Firm Value of Tourism and Hospitality Companies. (November 2021) - Yang, Shuai; Liu, Yahui; Wu, Xiaojun
Engaging customers via social media networking has become a rising trend of investments for tourism and hospitality firms. This new trend is termed "social media engagement." However, whether social media engagement can actually lead to increased financial value for tourism and hospitality firms is doubted. This study theorizes and empirically examines the relationship between social media engagement and intangible value of tourism and hospitality firms, and the joint effects of social media engagement and advertising investments on firm value. Using a daily longitudinal data set from tourism and hospitality firms that have issued domestic A-shares in China, this study finds that social media engagement has a significant and positive relationship with the firm value of tourism and hospitality companies. However, the two types of investments interact as substitutes, such that increasing advertising investments attenuate the beneficial effect of social media engagement on firm value.